The Burden of Criminal Procedural Proof - VAPNIARCHUK, Viacheslav V.; KAPLINA, Oksana V.; TITKO, Ivan A.; MARYNIV, Volodymyr I.; LAZUKOVA, Oksana V. (Journal of Advanced Research in Law and Economics, 2019)
The urgency of the article stated in the article is due to the need to revise traditional scientific views on certain peculiarities of criminal procedural evidence in connection with the expansion of the adversarial nature of domestic criminal proceedings. The purpose of the paper is to determine the essence of the category ‘burden of proof’ and justify the necessity of introducing it into scientific and law enforcement circulation. The main approach to the study of this problem was to carry out a critical analysis of the norms of the current criminal procedural legislation that regulates the requirements regarding the burden of proof and the views expressed on their proper understanding and application. The publication expresses the view that the distinction between such legal categories as ‘burden of proof’ and ‘burden of proof’ is proposed, the definition of the concept of ‘burden of proof’ is proposed and the rules for burden sharing between parties of criminal proceedings are analyzed. The material of the article represents both theoretical and practical value. They can be used for further research into the essence of the concept of ‘burden of proof’, as well as for proper understanding and enforcement of criminal procedural law enforcement activities.